(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes from a philosophical point of view the role of musical heritage in the integrative improvement of the qualities of ideological unity among young people. At the same time, ways of rationally using musical works of Central Asian thinkers in the formation of qualities of ideological unity and integration in young people will be shown.